2014
DOI: 10.3399/bjgp14x677149
|View full text |Cite
|
Sign up to set email alerts
|

Quality deviations in cancer diagnosis: prevalence and time to diagnosis in general practice

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 31 publications
(37 reference statements)
3
53
0
Order By: Relevance
“…Up to a third of all cancer patients experience at least one QD during the pre‐diagnosis (Jensen, Nissen, & Vedsted, ; Jensen, Sperling, et al, ). It has been shown that patients having experienced a QD during the primary diagnostic phase have longer diagnostic interval (Jensen, Nissen, et al, ), as the main consequence of QDs is delay (Hickner et al, ). Hence, we may suspect that part of the increased diagnostic interval (and worse experiences) seen among non‐CPP patients can be explained by a delay caused by more QDs in this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to a third of all cancer patients experience at least one QD during the pre‐diagnosis (Jensen, Nissen, & Vedsted, ; Jensen, Sperling, et al, ). It has been shown that patients having experienced a QD during the primary diagnostic phase have longer diagnostic interval (Jensen, Nissen, et al, ), as the main consequence of QDs is delay (Hickner et al, ). Hence, we may suspect that part of the increased diagnostic interval (and worse experiences) seen among non‐CPP patients can be explained by a delay caused by more QDs in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that one-third of the differences in patient experiences between referral routes could be explained by differences in reported QDs. Up to a third of all cancer patients experience at least one QD during the pre-diagnosis (Jensen, Nissen, & Vedsted, 2014;Jensen, Sperling, et al, 2015). It has been shown that patients having experienced a QD during the primary diagnostic phase have longer diagnostic interval (Jensen, Nissen, et al, 2014), as the main consequence of QDs is delay (Hickner et al, 2008).…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…7 Delayed diagnosis may occur if the GP attributes symptoms or abnormal test results to a health problem other than cancer. 8 Some patients may then experience a prolonged and dissatisfying diagnostic pathway 9 and may express their dissatisfaction through a change of practice (COP).…”
Section: Introductionmentioning
confidence: 99%
“…This accords to some extent with international studies of missed opportunities in cancer diagnosis 29 30. In the UK, the updated NICE guidance explicitly recognises that patients with combinations of common symptoms may be more likely to have lung cancer than patients with any one of these symptoms alone,28 31 but patients may not volunteer all the symptoms they experience in consultations, perhaps due to real or perceived time constraints in the consultation 31.…”
Section: Discussionmentioning
confidence: 99%